2010
DOI: 10.3109/00016349.2010.484042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intrapartum epidural analgesia at high altitudes: maternal, fetal, and neonatal outcomes. A randomized controlled trial of two formulations of analgesics

Abstract: At high altitudes, no major advantage was found for epidural ropivacaine over bupivacaine in addition to fentanyl for labor analgesia and no harmful effects of the medications were found on mothers, fetuses, or newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…There was a significantly faster onset of sensory block with ropivacaine compared to bupivacaine (5.67 min versus 6.67min, p = 0.0013). Shokry et al 7 compared 0.125% bupivacaine and 0.2% ropivacaine, each with Fentanyl 100 µg and found a faster onset of sensory block with ropivacaine like in our study. Contrary to our findings, Bawdane et al's 8 double blind comparison of 0.1% ropivacaine to 0.1% bupivacaine each with Fentanyl for labor analgesia showed that both the drugs were similar in respect to the onset of sensory blockade.…”
Section: Discussionsupporting
confidence: 75%
“…There was a significantly faster onset of sensory block with ropivacaine compared to bupivacaine (5.67 min versus 6.67min, p = 0.0013). Shokry et al 7 compared 0.125% bupivacaine and 0.2% ropivacaine, each with Fentanyl 100 µg and found a faster onset of sensory block with ropivacaine like in our study. Contrary to our findings, Bawdane et al's 8 double blind comparison of 0.1% ropivacaine to 0.1% bupivacaine each with Fentanyl for labor analgesia showed that both the drugs were similar in respect to the onset of sensory blockade.…”
Section: Discussionsupporting
confidence: 75%
“…Shokry et al ( 18 ) compared two groups receiving 0.125% bupivacaine and 0.2% ropivacaine, each with fentanyl 100 µg and found an non-significant faster onset of action and significantly shorter duration of analgesia in the ropivacaine group. In contrast, Chora and Hussain ( 4 ) showed significantly faster onset of analgesia in the bupivacaine group and longer duration in the ropivacaine group.…”
Section: Discussionmentioning
confidence: 99%